University of Virginia records - University of Virginia
Correspondence (1827-1828) and architectural plan of the university (undated). Includes letters from William B. Giles, governor of Virginia, and William H. Richardson notifying Joseph C. Cabell, John H. Cocke, and James Madison of meetings of the board of visitors; and testimonials in behalf of Thomas W. Clerke, applicant for a chair in law. Other correspondents include Gesner Harrison, Chapman Johnson, Thomas P. Jones, Richard Henry Lee, and Robert M. Patterson
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Cabell, Joseph C. -- 1778-1856 -- Correspondence; Clerke, Thomas W; Cocke, John Hartwell, -- 1780-1866 -- Correspondence; Giles, William Branch, -- 1762-1830 -- Correspondence; Harrison, Gesner -- Correspondence; Johnson, Chapman, -- 1779-1849 -- Correspondence; Jones, Thomas P., -- 1774-1848 -- Correspondence; Lee, Richard Henry, -- 1794-1865 -- Correspondence; Madison, James, -- 1751-1836 -- Correspondence; Patterson, Robert M. -- 1787-1854 -- Correspondence; Richardson, William H. -- 1795-1876 -- Correspondence; University of Virginia. -- Buildings; University of Virginia. -- Board of Visitors; University of Virginia. -- School of Law -- Faculty